Sliding Mode Disturbance Observer-Based Fractional Second-Order Nonsingular Terminal Sliding Mode Control for PMSM Position Regulation System. (14th January 2015) - Li, Hong-Ru; Jiang, Zhi-Bin; Kang, Nan
Abstract : This paper investigates the position regulation problem of permanent magnet synchronous motor (PMSM) subject to parameter uncertainties and external disturbances. A novel fractional second-order nonsingular terminal sliding mode control (F2NTSMC) is proposed and the finite time stability of the closed-loop system is ensured. A sliding mode disturbance observer (SMDO) is developed to estimate and make feedforward compensation for the lumped disturbances of the PMSM system. Moreover, the finite-time convergence of estimation errors can be guaranteed. The control scheme combining F2NTSMC and SMDO can not only improve performance of the closed-loop system and attenuate disturbances, but also reduce chattering effectively. Simulation results show that the proposed control method can obtain satisfactory position tracking performance and strong robustness.